Relações entre a percepção musical e o ensino das características das ondas sonoras - Stinglin, Douglas da Costa (2017)
The present work consists of a research in physics teaching, more specifically in acoustic teaching. A didactic sequence was applied in a first year high school class, contextualizing the concepts of acoustics in listening to music and living with noise pollution and using as theoretical framework the theory of meaningful learning developed by Ausubel. The objective was to apply the didactic sequence to obtain data regarding the learning of the concepts, analyzing whether or not they were significant facilitators. The audio recording of the classes and a questionnaire, applied at the beginning and at the end of the sequence, were used to analyze the before and after, besides the field diary, recorded by the author. The sequence consisted of six forty-five minute classes. The analysis of the data points to a facilitation of the significant learning of Acoustics. However, it would be important to continue the application of the data collection instruments to a larger audience and with more diverse class profiles, so that the results can lead to more conclusive and comprehensive results.